The Effect of Motivation and Occupational Safety and Health (OSH) on Performance Through Job Satisfaction as a Mediating Variable among Employees of TM Systems International Trading (Shanghai) Co., Ltd., in Pelalawan Regency - Putri, Ariza; Rasyid , Rosyeni (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
Human resources are strategic assets essential for achieving organizational goals, with employee performance influenced by abilities, skills, and psychological, social, and work environment factors. This study analyzes the impact of motivation and Occupational Safety and Health (OSH) on employee performance through job satisfaction as a mediating variable among employees of TM Systems International Trading (Shanghai) Co., Ltd. in Pelalawan Regency. Using a quantitative approach and census technique with 136 respondents, data were analyzed via Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS. Results show that both motivation and OSH positively and significantly influence job satisfaction. Higher motivation levels and effective OSH implementation correspond to increased job satisfaction. However, motivation and OSH do not directly affect employee performance but influence it indirectly through job satisfaction. Moreover, job satisfaction directly and significantly impacts employee performance, confirming its role as a psychological link between motivation, OSH, and performance improvement. These findings demonstrate that to enhance employee performance, companies must strengthen policies that boost motivation, consistently enforce OSH systems, and foster a safe, comfortable work environment. By doing so, they increase job satisfaction, which in turn drives productivity and performance. In summary, elevating motivation and effectively implementing OSH contribute to continuous employee performance improvement via enhanced job satisfaction.